Evaluasi Aksesibilitas Fasilitas Penyandang Tunadaksa dan Tunanetra di Stasiun Duri Menggunakan Metode Promethee - Dzaky, Hanif Muhammad; Leliana, Arinda; Priyanto, Sapto (Universitas Ibn Khaldun, 2026)
Duri Station is a transit station for KRL passengers Commuter Line Tangerang-Duri PP, KRL relations Commuter Line loop line Cikarang, and Commuter Line Soekarno-Hatta Airport with an average passenger capacity of ±10,000 passengers/day. Overcrowding often occurs and causes the movement of passengers and people with disabilities to become hampered. This research aims to evaluate the suitability of special facilities for the disabled and visually impaired at Duri Station, rank proposals for improvements and development of special facilities for the disabled and visually impaired at Duri Station, and provide recommendations to Duri Station regarding special facilities for the disabled and visually impaired that need immediate improvement and development. This research uses the method purposive sampling to select respondents based on specific criteria used as samples in this research. Data processing is carried out using the method PROMETHEE to assess and rank the facilities that need immediate repair and improvement at Duri Station. The research results show that several facilities at Duri Station, such as platforms, waiting rooms, disabled toilets, prayer rooms, lifts, ramps, guideways/guiding block, and the disability counter does not comply with the provisions stated in PM No. 63 of 2019 and PUPR Ministerial Decree no. 14/PRT/M 2017. Ranking using method PROMETHEE resulting in a priority ranking for improving facilities for the disabled according to users, namely increasing sufficient free space in disabled toilets for wheelchair users to maneuver 180° and to open and close doors with a value net flow of -0.396. The main priority for the blind that needs to be improved and improved is the availability of priority seats in the Duri Station waiting room with mark net flow of -0.663.